Highly Conserved Testicular Localization of Claudin-11 in Normal and Impaired Spermatogenesis - Stammler, Angelika; Lüftner, Benjamin Udo; Kliesch, Sabine; Weidner, Wolfgang; Bergmann, Martin; Middendorff, Ralf; Konrad, Lutz; Justus Liebig University Giessen (My University, 2016)
In this study we tested expression of tight junction proteins in human, mouse and rat and analyzed the localization of claudin-11 in testis of patients with normal and impaired spermatogenesis. Recent concepts generated in mice suggest that the stage-specifically expressed claudin-3 acts as a basal barrier, sealing the seminiferous epithelium during migration of spermatocytes. Corresponding mechanisms have never been demonstrated in humans. Testicular biopsies (n = 103) from five distinct groups were analyzed: normal spermatogenesis (NSP, n = 28), hypospermatogenesis (Hyp, n = 24), maturation arrest at the level of primary spermatocytes (MA, n = 24), Sertoli cell only syndrome (SCO, n = 19), and spermatogonial arrest (SGA, n = 8). Protein expression of claudin-3, -11 and occludin was analyzed. Human, mice and rat testis robustly express claudin-11 protein. Occludin was detected in mouse and rat and claudin-3 was found only in mice. Thus, we selected claudin-11 for further analysis of localization. In NSP, claudin-11 is located at Sertoli-Sertoli junctions and in Sertoli cell contacts towards spermatogonia. Typically, claudin-11 patches do not reach the basal membrane, unless flanked by the Sertoli cell body or patches between two Sertoli cell bodies. The amount of basal claudin-11 patches was found to be increased in impaired spermatogenesis. Only claudin-11 is expressed in all three species examined. The claudin-11 pattern is robust in man with impaired spermatogenesis, but the proportion of localization is altered in SCO and MA. We conclude that claudin-11 might represent the essential component of the BTB in human.
Keywords: ddc:610